Recent advances of endoscopic retrograde cholangiopancreatography using balloon assisted endoscopy for pancreaticobiliary diseases in patients with surgically altered anatomy: Therapeutic strategy and management of difficult cases. Issue 6 (17th November 2020) - Shimatani, Masaaki; Mitsuyama, Toshiyuki; Tokuhara, Mitsuo; Masuda, Masataka; Miyamoto, Sachi; Ito, Takashi; Nakamaru, Koh; Ikeura, Tsukasa; Takaoka, Makoto; Naganuma, Makoto; Okazaki, Kazuichi
Abstract : Endoscopic retrograde cholangiopancreatography (ERCP) is an endoscopic modality established for diagnosis and treatment of pancreaticobiliary diseases. However ERCP in patients with surgically altered anatomy (SAA) has been difficult, and more invasive therapies have been primarily selected. The development of balloon assisted endoscopes (BAEs) innovatively facilitated ERCP in such patients. Recent advances of BAEs and other devices greatly contributed to increasing success of ERCP using BAEs (BAE‐ERCP). Furthermore, interventions using Endoscopic Ultrasound (EUS‐intervention) have been reported to be useful for pancreaticobiliary diseases in patients with SAA, which provide more options for endoscopic therapies and are also expected as a rescue therapy for difficult cases of BAE‐ERCP. In order to thoroughly complete endoscopic treatment for pancreaticobiliary diseases with SAA, it is important to standardize the BAE‐ERCP procedures based on the features of respective endoscopes and to establish a strategy for endoscopic treatment which includes analysis of BAE‐ERCP difficult cases and selection of cases for rescue therapy. In addition, it is essential to be acquainted with the characteristics of possible adverse events of the procedure and to be able to deal with them for safe accomplishment of endoscopic treatment.